Reconstructing Careers: New Deals for Old: Rhetoric or Reality ? - Adamson, Stephen (Cranfield University, 2002)
From the late 1980s to the mid-1990s economic and technological forces created significant pressure on organisations to downsize and delayer in order to maximise asset utilisation, retain competitive advantage and, literally in some cases, survive. In the wake of these changes it seemed the classic, bureaucratic organisational career was also under threat of survival as organisations were no longer able to offer a job for life, and with it the promise of regular hierarchical progression. Thus, the 'death' of the traditional career was proclaimed. As a result, academics began to assert that we were witnessing a fundamental redefinition of the individual-organisation relationship, and that the new imperative was to re-contract with individuals, rebuild trust, and thus strike up a new deal. This talk of the demise of the career and, with it, the old, relational 'deal' began to take on the character of a universalistic truth, and by the mid-1990s academics and practitioners alike were widely announcing the arrival of 'the New Deal'. This research offers a challenge to this pervasive rhetoric. It is argued that analysis of employees' own talk on the issue at an important historical point in the new deal storyline indicates a much more contextually- specific and emergent phenomenon than the rhetoric implies. In pursuit of this broad aim, the research takes a contextualist-interpretivist, theory- generating approach. More specifically, from the perspective of Social Constructionism it is argued that we can only talk of the emergence of new deals when such deals are part of employees' daily realities, as evinced by their talk about careers. The foundation of the research is twenty four semi-structured interviews, coupled with in-depth analyses of the two case study organisations in which this data were generated: the Bank of England and IBM (UK) Limited. Discourse Analysis represents the theoretic al/methodological lens through which the data are analysed, and thus the actual talk of subjects in each case study organisation is presented in order to consider the organisation and function of their talk. The emphasis, however, is on the discourses evident in (or absent from) subjects' talk and, in particular, the vocabularies of 'new' and 'old' deals. The contributions of the research can be expressed as follows. First, by catching employees at the cusp of the change process in each of the case study organisations, the research makes a unique, processual contribution to our understanding of the apparent demise of the 'old deal' and emergence of the 'new' in two specific contexts. By examining individuals' own talk of these changes, and of the implications for their careers, it shows how their understandings were changing. Second, the research points up the distinction between linguistic elements (discourses, interpretative repertoires, vocabularies) that were context-specific, and thus culturally forined, versus those that were transcontextual and emergent in subjects' talk and which were therefore likely to be present, or continue to emerge, after the new deal had become a 'reality'. Thus, the research indicates how assumptions about careers change over the longer term and how new perspectives do and will continue to emerge. Third, the research makes a methodological contribution to the field, principally in its illustration of the application of Discourse Analysis and its ability to raise 'novel' questions for those concerned with the nature of the subjective career.